DEVELOPING STUDENTS’ ABILITIES THROUGH TEACHING WITH PEDAGOGICAL TECHNOLOGIES (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article discusses teaching students how to draw drawings, read them using different methods, and approach them didactically, as well as developing students’ abilities through the use of pedagogical technologies to increase their activity in the classroom while improving the knowledge and skills they acquire in technical drawing.
Keywords: technical drawing, environment, space, form, pedagogical technology, ability, implementation, continuity, efficiency, graphic literacy.